Association between dietary minerals and glioma: A case-control study based on Chinese population - Zhang, Weichunbai; He, Yongqi; Kang, Xun; Wang, Ce; Chen, Feng; Kang, Zhuang; Yang, Shoubo; Zhang, Rong; Peng, Yichen; Li, Wenbin (Frontiers in Nutrition, 2023)
Background: As one of the essential nutrients for the human body, minerals participate in various physiological activities of the body and are closely related to many cancers. However, the population study on glioma is not sufficient. Objective: The purpose of this study was to evaluate the relationship between five dietary minerals and glioma. Methods: A total of 506 adult patients with glioma and 506 healthy controls were matched 1:1 according to age (± 5 years) and sex. The food intake of the subjects in the past year was collected through the food frequency questionnaire, and the intakes of calcium, magnesium, iron, zinc, and copper in the diet were calculated. The logistic regression model was used to estimate the odds ratio (OR) and 95% confidence interval (95% CI) for dietary minerals to gliomas. Results: After adjusting for confounders, higher intakes of calcium (OR= 0.65, 95%CI: 0.57-0.74), magnesium (OR=0.18, 95%CI: 0.11-0.29), iron (OR=0.04, 95%CI: 0.02-0.11), zinc (OR=0.62, 95%CI: 0.54-0.73), and copper (OR=0.22, 95%CI: 0.13-0.39) were associated with a significantly decreased risk of glioma. Similar results were observed in gliomas of different pathological types and pathological grades. The restriction cubic spline function suggested significant linear dose-response relationships between intakes of five minerals and the risk of glioma. When the dietary minerals exceeded a particular intake, the risk of glioma stabilized. Conclusion: Our study suggests that higher dietary intakes of calcium, magnesium, iron, zinc, and copper are associated with a decreased risk of glioma. However, the results of this study require further exploration of potential mechanisms in the future better to elucidate the effects of mineral intake on gliomas.